Rule of Law, Corporate Governance and AI Humanoid Robots: Charting the Course for a Global Regulatory Framework - Tayewo A. Adewumi (Mizan law review, 2025)
On July 7, 2023, a panel of robots told reporters in Geneva, Switzerland, that they could be more efficient leaders than human beings. The nine artificial intelligent (AI) humanoid robots said they would not take anyone's job or stage a rebellion. Four months later, on Monday 13 November 2023, News Direct reported that the world’s first AI humanoid robot CEO entered the boardroom. The above events show the advent of artificial intelligent humanoid robots which are likely to become substitutes for humans in corporate and general governance. This article recommends a global regulatory framework for the manufacture, use, and operation of AI humanoid robots. The author argues that allowing the development and operation of AI humanoid robots for governance without adequate international regulation would spell doom to human existence. Artificial intelligent humanoid robots should not be allowed to override human natural intelligence but to complement it and this can be done through global regulation. A regulatory framework for AI systems has already started (in June 2024) with the advent of the European Union Artificial Intelligence Regulation (Regulation (EU) 2024/1689). The way forward envisages that the United Nations General Assembly will follow the footsteps of the European Union.